2021
DOI: 10.1088/1674-4926/42/7/072202
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the order–disorder phase transition in a Cs2NaFeCl6 double perovskite towards reversible thermochromic application

Abstract: Multifunctional lead-free double perovskites demonstrate remarkable potential towards applications in various fields. Herein, an environmentally-friendly, low-cost, high-throughput Cs2NaFeCl6 single crystal with exceedingly high thermal stability is designed and grown. It obtains a cubic lattice system in the temperature range of 80–500 K, accompanied by a completely reversible chromatic variation ranging from yellow to black. Importantly, the intriguing thermochromism is proved to own extremely high reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…For the first theoretical curve (see the orange curves), the quasi-harmonic (QH) approximation is applied, where the temperature-induced frequency shift is evaluated only by expanding the volume of the structure, following the measured thermal expansion. 22 Even though this approximation can reasonably describe the experimentally measured frequency shifts of the A 1 g , E g , and T 2 g _ Cs modes, it predicts a strong downward shift of the T 2 g mode (see the orange squares in Figure 3 b), which is not observed experimentally. For the second theoretical curve (see the green curves), we include, in addition to the volumetric thermal expansion, the effect of intrinsic anharmonicity, i.e., phonon–phonon interactions, using a self-consistent phonon (SCPH) methodology 37 − 39 (see also Methods and Supporting Information ).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…For the first theoretical curve (see the orange curves), the quasi-harmonic (QH) approximation is applied, where the temperature-induced frequency shift is evaluated only by expanding the volume of the structure, following the measured thermal expansion. 22 Even though this approximation can reasonably describe the experimentally measured frequency shifts of the A 1 g , E g , and T 2 g _ Cs modes, it predicts a strong downward shift of the T 2 g mode (see the orange squares in Figure 3 b), which is not observed experimentally. For the second theoretical curve (see the green curves), we include, in addition to the volumetric thermal expansion, the effect of intrinsic anharmonicity, i.e., phonon–phonon interactions, using a self-consistent phonon (SCPH) methodology 37 − 39 (see also Methods and Supporting Information ).…”
Section: Resultsmentioning
confidence: 86%
“…We show two separate theoretical curves. For the first theoretical curve (see the orange curves), the quasi-harmonic (QH) approximation is applied, where the temperature-induced frequency shift is evaluated only by expanding the volume of the structure, following the measured thermal expansion . Even though this approximation can reasonably describe the experimentally measured frequency shifts of the A 1 g , E g , and T 2 g _ Cs modes, it predicts a strong downward shift of the T 2 g mode (see the orange squares in Figure b), which is not observed experimentally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, cesium sodium iron chloride (Cs 2 NaFeCl 6 ) single crystals were introduced as a new promising lead‐free double perovskite material for thermochromic applications. [ 12 ] It has been shown that this perovskite has a bandgap of 2.07 eV at room temperature (RT) and exhibits promising absorption in the visible region. [ 13 ] Furthermore, doping Cs 2 NaFeCl 6 with small amounts of silver (Ag) resulted in significant changes in structural and optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, five regulation modes were commonly made to accommodate the optical properties of organic–inorganic hybrid perovskites: temperature regulation, , chemical composition regulation, ion-doping regulation, structural dimension regulation, , and heterostructure regulation. However, despite some progress that has been made in studying the regulation of the optical properties of organic–inorganic hybrid perovskite materials, the present regulation strategies of optical properties are mainly limited to changing the chemical composition and ion doping. As for structural dimension regulation, it still has great potential to investigate.…”
Section: Introductionmentioning
confidence: 99%